A formação em ensino da matemática nos cursos de pedagogia - Chagas, Bergson Lucena da (Universidade Federal Rural do Semi-Árido, 2021)
When comparing the results in Mathematics of large-scale performance evaluations such as the SAEB, of 5th and 9th grade students, it is easy to see that there is an evolution in learning. On the other hand, the large number of students who have different learning difficulties in Mathematics is also a fact. In this work we do a bibliographical and documental research, and through these and the analysis of the curricular grids of three of the main Pedagogy courses that are developed in Mossoró-RN, from the results of the grades mentioned in Mathematics in the last five editions of the SAEB and a questionnaire sent to teachers of kindergarten and early grades of elementary school, we tried to answer the position of mathematics teaching in pedagogy courses. The results show us that they are no different from those that happen in other regions at the national level, revealing that the teaching of mathematics occupies a place far below what is necessary for the training of teachers in the initial grades, at the beginning of their cognitive and form first concepts in this discipline.
Keywords: Matemática; Pedagogia; Dificuldades de aprendizagem; SAEB; Math; Pedagogy; Learning difficulties; SAEB; CIENCIAS EXATAS E DA TERRA::MATEMATICA